INFORMATION COMMUNICATION TECHNOLOGY (ICT) DEPLOYMENT AND BANK PERFORMANCE IN NIGERIA - Prof. Umebali, E. E.; Jimoh, Abdul Miniru (Journal of the Management Sciences, 2023)
This study examined the effect of information and communication technology (ICT) deployment and bank performance in Nigeria. The objectives of the study were to examine the effect of automated teller machine (ATM), point of sale (POS) and Mobile Pay (MPay) on bank performance in Nigeria. Using secondary data sourced from central bank of Nigeria website, the study employed the ordinary least square regression method to carry out the analysis. The findings revealed that, automated teller machine (ATM), point of sale (POS) and Mobilepay have significant effects on Banks performance in Nigeria. It is recommended, among others, that for effectiveness in electronic banking through the adoption of ICT, there should be rigorous campaign and awareness for clients to patronize electronic banking facilities (ATM, POS and MOBILE PAY) for them to fully reap the benefit of ICT.